Porous Materials for Environmental Applications - Gil Bravo, Antonio; Vicente, Miguel A. (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
The development of porous materials has attracted the attention of the research community for years. Porosity characteristics have specific impacts on the material properties and materials that are applied in many areas, such as pollutant removal, CO2 capture, energy storage, catalytic oxidation and reduction processes, the conversion of biomass to biofuels, and drug delivery. Examples of porous materials are activated carbons, clays, and zeolites. The aim of this book is to collect the recent advances and progress regarding porous materials and their applications in the environmental area.